2016
DOI: 10.3390/ijms17111881
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis Identifies Key Candidate Genes Mediating Purple Ovary Coloration in Asiatic Hybrid Lilies

Abstract: Lily tepals have a short lifespan. Once the tepals senesce, the ornamental value of the flower is lost. Some cultivars have attractive purple ovaries and fruits which greatly enhance the ornamental value of Asiatic hybrid lilies. However, little is known about the molecular mechanisms of anthocyanin biosynthesis in Asiatic hybrid lily ovaries. To investigate the transcriptional network that governs purple ovary coloration in Asiatic hybrid lilies, we obtained transcriptome data from green ovaries (S1) and purp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…This result suggests that the up-regulation of the structural genes of the anthocyanin pathway might responsible for the purple pigmentation in the leaves of purple ornamental cabbage. Similar results were found by Xu et al [ 40 ] for purple pigmentation in the ovary of Asiatic hybrid lilies. Xu et al [ 27 ] reported that the formation of purple bases in the bicolor tepals of the lily cultivar ‘Tiny Padhye’ was due the up-regulation of structural genes of the anthocyanin pathway.…”
Section: Discussionsupporting
confidence: 91%
“…This result suggests that the up-regulation of the structural genes of the anthocyanin pathway might responsible for the purple pigmentation in the leaves of purple ornamental cabbage. Similar results were found by Xu et al [ 40 ] for purple pigmentation in the ovary of Asiatic hybrid lilies. Xu et al [ 27 ] reported that the formation of purple bases in the bicolor tepals of the lily cultivar ‘Tiny Padhye’ was due the up-regulation of structural genes of the anthocyanin pathway.…”
Section: Discussionsupporting
confidence: 91%
“…Primers for ACT were previously described (Xu et al, 2016). Primer pairs for genes were designed using Primer Premier 5.0 software 1 with the following parameters: melting temperatures (T m ) of 55–65°C, primer lengths of 17–25 bp, and amplicon lengths of 100–300 bp ( Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…These formation mechanisms have also attracted extensive attention in the study of ornamental plants. Additionally, studies on the regulatory gene of flower color in lily have shown that LhMYB12 promotes the coloring of whole petals [25,26]; LhMYB12-lat determines the formation of anthocyanin in ovary [27]; LrMYB15 regulates anthocyanin pigmentation in bud in Lilium regale [28]; and LhMYB18 is involved in the formation of large anthocyanin spots [29]. The lily cultivar 'Vivian', which is an Oriental hybrid lily, is fragrant, brightcolored and is highly desired by consumers.…”
Section: Introductionmentioning
confidence: 99%